VD_FINDINFO HC / 2015 / 886 vom 29. September 2015 - VD Tribunal cantonal (2015)
PROROGATION DE FOR, ACCEPTATION TACITE DE COMPÉTENCE, AUTORITÉ DE CONCILIATION | 17 CPC (CH), 18 CPC (CH), 59 al. 2 let. b CPC (CH)